Mould flow and component design analysis of polymeric based composite automotive clutch pedals - Syed Shaharuddin, Sharifah Imihezri; Salit, Mohd Sapuan; Sulaiman, Shamsuddin; Megat Ahmad, Megat Mohamad Hamdan; Zainuddin, Edi Syams; Osman, Mohd Rasid; Abdul Rahman, Mohd Zaki (2006)
Mould flow and component design analysis of polymeric based composite automotive clutch pedals are presented in this paper. This paper studies the differences between the two types of profile with and “I” and “T” cross-sections using finite element analysis software package called LUSAS. Based on the study, an “I” cross-section is able to endure higher stress compared to “T” profile. It also evaluates the differences between an “X” and “V” rib patterns also based on finite element analysis (FEA) as well as mould flow analysis using Moldflow Plastic Insight (MPI) software. The two patterns are compared in terms of stress and flow patterns. Based on the results, a “V” rib is integrated into the composite clutch pedal.